Sejarah Kebudayaan: Hasil Budaya Material dan Non-Material Akibat Adanya Pengaruh Islam di Nusantara - Alfain Nur Mustawhisin; Rully Putri Nirmala P; Wiwin Hartanto (LP4MK STKIP PGRI Lubuklinggau, 2019)
Indonesia is a country with diverse cultures that live side by side in it. There are various factors that influence the diversity of cultures that Indonesia has, one of which is the influence of foreign parties, it has been known that Indonesia was once influenced by Hindu and Buddhist culture in a long period of time and has instilled cultural values ​​in Indonesia, after influence Hindu and Buddhist culture declined, came new cultures and influences brought by Islam. The arrival of Islam in the form of the influence of religion and culture does not necessarily erase the Indonesian original culture or culture resulting from the acculturation of Hinduism and Buddhism and Indonesia. The arrival of Islam that uses peaceful means tends to be more easily accepted by Indonesian people, by means of Islam that comes peacefully and does not impose its influence and culture, then slowly the development of Islam in Indonesia can develop rapidly, and another way that Islam uses is to alienate culture existing ones with teachings that are considered to be in accordance with Islamic law, so that unconsciously people are led to use Islamic methods through existing cultures, which is why later Indonesian cultures will emerge that are influenced by the existence of Islam in Indonesia, both in material and non-material forms.